JURIDICAL ANALYSIS OF NON-INTERVENTION PRINCIPLE IN THE UNITED NATIONS CHARTER 1945 (CASE STUDY UNITED NATIONS CONDEMNATION) OF THE SYARI’AH ENAL CODE IN BRUNEI DARUSSALAM - Riswana Pratiwi; Lena Farsia (Fakultas Hukum Universitas Syiah Kuala, 2022)
Abstract – This paper aims to understand the elements that cause an international organization to intervene in the affairs of other countries, to understand that the United Nations criticism of the implementation of Brunei's Sharia law does not violate the non-intervention principle under Article 2(7) of the UN Charter. This study uses a normative legal approach. The outcomes of this study found that there are three elements of an international organization that can intervene in the problems of other countries. The first arises because of a relationship regulated by conventional international law, the second arises because of an employment relationship. The third arises because of the enactment of a transnational legal system that involves third parties, either with private parties, organizations, or the state. On the other hand, based on the principle of Brunei's membership in the United Nations, the United Nations condemnation of Brunei is only an ordinary warning that does not contain an element of coercion in action. which means it does not violate the non-intervention principle in Article 2(7) of the Charter. It is recommended for the United Nations to make an additional regulatory protocol that contains clear boundaries and a clear understanding of the intervention. Then reduce excessive attention to domestic problems in other countries if it is found that citizens of their own country do not have a problem with it. Because in general, intervention actions that have not found a clear point and are still widely debated are sensitive. So from various parties, especially the United Nations, to be able to restrain their enthusiasm for something that smells domestic.Keywords : Non-intervention principle, Syari’ah Penal Code Order, United Nations Charter